The ins and arounds in the U.S. housing market - Rüdiger Bachmann; Daniel Cooper (Federal Reserve Bank of Boston, 2014)
In the United States, 15 percent of households change residence in a given year. This result is based on data from the Panel Study of Income Dynamics on gross flows within and between the two segments of the housing market-renter-occupied properties and owner-occupied properties. The gross flows between these two segments are four times larger than the net flows. From a secular perspective, housing turnover exhibits a hump-shaped pattern between 1970 and 2000, which this paper attributes to changes in the age composition of the U.S. population. At higher frequencies, housing turnover is procyclical and tends to lead the business cycle and real house prices. By taking a two-segment view of the U.S. housing market and by carefully documenting the empirics of turnover within and between these segments, the paper provides important moments for and gives empirical guidance to the design, calibration, and evaluation of micro-founded, dynamic, and quantitative models of the U.S. housing market.
Keywords: E30; E32; R21; 330; housing market; PSID; turnover; net and gross flows